Hubungan antara Kebiasaan Sarapan dengan Tingkat Memori pada Siswa Sekolah Dasar Negeri di Kota Denpasar - I Putu Hendri Aryadi; Ketut Ariawati; I Gusti Ngurah Made Suwarba (Sekretariat Badan Penelitian dan Pengembangan Kesehatan, 2019)
Abstract Breakfast is believed to provide many benefits to the growth and development of children, including its memory, but the availability of data that can convince the public regarding this matter is still relatively lacking. This analytic study was conducted to determine the relationship between breakfast habits and memory levels in public elementary school students in the city of Denpasar, with a cross- sectional approach. The research data were primary data obtained from interviews with demographic questionnaire, Breakfast Consumption Habit Questionnaire (BCHQ) for the assessment of chidlren’s habists and Children’s Memory Questionnaire-Revised (CMQ-R) for assessing children’s memory levels. The implementation of study is from May-December 2018 to 16 public elementary schools in Denpasar City. The sample collection technique using cluster random sampling method with a sample size of 399 students. The sample in this study was dominated by male (55.1%) with the majority aged 10 years and above (57.4%). As many as 40.8% of students are classified as malnourished (underweight, overweight, and obese). The economic status of the respondents’ family is dominated by middle class. The majority of the father and mother of each respondents were high school graduates (59.1% and 53.4%), with the most jobs being private employee (39.1%) and not working (30.6%) respectively. More than a third of respondents (37.3%) were not used to have breakfast. Children who are accustomed to breakfast tend to have higher memory levels of 1.737 times more than those are not used to it. Breakfast habits have a significant relationship with the level of memory of children, with a value of p=0.008 (95% CI= 1,153–2,618). Breakfast habits are proven to be a factor that affects the level of memory of children. Further research is needed to find out the specific memory aspect that are affected and the type of breakfast that is most ideal for children development. Abstrak Sarapan dipercaya memberikan banyak manfaat pada tumbuh kembang anak, termasuk memorinya, akan tetapi kesediaan data yang dapat meyakinkan masyarakat terkait hal tersebut masih relatif kurang. Penelitian analitik ini dilakukan untuk mengetahui hubungan antara kebiasaan sarapan dan tingkat memori pada siswa sekolah dasar negeri di Kota Denpasar, dengan pendekatan potong lintang. Data penelitian adalah data primer yang diperoleh dari hasil wawancara dengan kuesioner demografik, Breakfast Consumption Habit Questionnaire (BCHQ) untuk penilaian kebiasaan sarapan anak serta Children’s Memory Questionnaire-Revised (CMQ-R) untuk penilaian tingkat memori anak. Pelaksanaan penelitian yaitu dari bulan Mei-Desember 2018 di 16 Sekolah Dasar Negeri (SDN) di Kota Denpasar. Teknik pengumpulan sampel dengan metode sampling acak klaster dengan jumlah sampel 399 orang siswa. Sampel pada penelitian ini didominasi oleh laki-laki (55,1%), dengan sebagian besar berusia 10 tahun ke atas (57,4%). Sebanyak 40,8% siswa tergolong malnutrisi (underweight, overweight, dan obesitas). Status ekonomi keluarga responden didominasi oleh golongan menengah. Ayah dan ibu dari masing-masing responden sebagian besar adalah lulusan SMA (59,1% dan 53,4%), dengan pekerjaan terbanyak yaitu sebagai pegawai swasta (39,1%) dan tidak bekerja (30,6%) berturut-turut. Lebih dari sepertiga responden (37,3%) tidak terbiasa sarapan. Anak yang terbiasa sarapan cenderung memiliki tingkat memori lebih tinggi 1,737 kali lebih banyak daripada yang tidak terbiasa. Kebiasaan sarapan memiliki hubungan yang bermakna dengan tingkat memori anak, dengan nilai p=0,008 (95% CI=1,153– 2,618). Kebiasaan sarapan terbukti mampu menjadi faktor yang mempengaruhi tingkat memori anak. Penelitian lebih lanjut diperlukan untuk mengetahui aspek memori spesifik yang dipengaruhi dan jenis sarapan yang paling ideal bagi tumbuh kembang anak.